Clinical faces of pulmonary tuberculosis - Rzymkowska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2006)
Tuberculosis is an infectious disease that has been known for centuries. Robert Koch had discovered Mycobacterium tuberculosis in 1882. Over the years, improvements in microbiology technology, clinical and radiologic patterns help us to understood and find most of cases of tb, but steel the disease has been reemerging. Tuberculosis may involve multiple organs such as the kidney, CNS, liver, spleen, and bone, but in 80-90% localized in lungs. Tb of the lung is devided to primary and postprimary tuberculosis. Primary tuberculosis is usually a self-limited infection. Most of cases of primary tuberculosis are asymptomatic. Patients with postprimary tuberculosis often manifest disease within 2 years of the initial infection or many years later, often as a result of comorbid states like malnutrition, kidney insufficiency, diabetes mellitus, old age, AIDS, immunosupression treatment or neoplasm.